Driving toward wellness: The synergy of stress monitoring in shaping the illness wellness continuum for truck drivers - Nurhadi, Ihsan; Darmawan, Bambang; Okitasari, Hanissa (INVOTEC, 2024)
There are numerous external costs associated with logistics that can potentially have an indirect influence on businesses or society as a whole. The purpose of this research paper is to provide an overview of the external costs related to the health of truck drivers and how it can potentially have a detrimental effect on supply chains. Truck drivers are vital contributors to the logistics and transportation sector and their role has a significant impact on the global economy. However, the demanding nature of their profession often leads them to neglect their own well-being and health, which in turn can have negative consequences for the drivers themselves, their companies, and the overall supply chains. This is a crucial issue that has unfortunately been largely overlooked in the existing literature on logistics and transportation. The objective of this paper is to identify the matter and propose a solution which involves monitoring the stress and fatigue levels of truck drivers in real-time using wearable device sensors and the Internet of Things. The aim is to create awareness within the logistics community and to encourage future research that can help mitigate the issues that may arise due to the presence of unhealthy truck drivers.